Spa therapy in the treatment of psoriasis - Rokowska-Waluch, Anita; Pielesiak, Anna; Pawlaczyk, Mariola (Dermatology Review/Przegląd Dermatologiczny, 2009)
Spa therapy is a therapeutic method used worldwide which takes advantage of the healing capacities of natural resources: water, air, sunlight, temperature, humidity and barometric pressure. It represents a safe and efficient alternative to pharmacological therapeutic methods. Different treatment modalities may be used alone or in various combinations and modifications, also combined with conventional topical medications. The major dermatological diseases that are frequently treated with spa therapy are psoriasis, atopic dermatitis and vitiligo. There have not been many randomized clinical studies comparing the efficacy of balneotherapy, phototherapy and balneophototherapy. Moisturizing of the skin before UVB and UVA radiation increases its beneficial effect.